Mental health and sleep: in COVID positive health care workers in India - A. V., Ramya; Arun, S.; Devi, Elsa Sanatombi; Vasanth, K. (International Journal of Research in Medical Sciences, 2023)
Background: Starting from Wuhan as a local transmission, COVID-19 turned out to be a pandemic affecting the entire global population either as a patient or at least being exposed to the novel corona virus. The present study has been done to see how much working to treat Covid patients has put stress, anxiety, depression and sleep disturbance on health care professional after becoming covid positive themselves, essentially their own life at risk. Methods: This was a prospective observational cross-sectional study done in Sri Manakula Vinayagar Medical College and Hospital, Puducherry, with ethics approval. Sample size was 145 health care workers who had covid infection. The study comprised of questions from Dass 21 questionnaire and Likert sleep scale. Results: Mild levels of stress was seen in 16 members (11.03%), moderate stress was seen in 3 members (2.06%). The chi square value was calculated as significant p value of 0.045. Mild anxiety was seen among 13 (8.96%), moderate anxiety seen in 23 (15.86%), severe anxiety was seen in 2 (1.37%), Extremely severe anxiety was seen in 1 individual (0.68%). Mild depression was seen in 12 (8.27%), moderate depression was seen in 14 (9.65%). The quality of sleep was rated on a 10-point scale, 5.5% had reported poor sleep, 53.8% reported moderate sleep disturbance. Conclusions: This study reveals that mental health issues are possible for medical professionals too and that anxiety needs to be addressed in health professionals too. More so when isolated from their families and friends.